Parenting Behavior Questionnaire revised (QEEP-r): Psychometric study and measurement invariance analysis for mothers and fathers - Cruz, Orlanda (2018)
The current study presents the Parenting Behavior Questionnaire revised (QEEP-r), which offers a measure of adolescents’ perceptions of father and mother’s parenting behaviors (as its first version QEEP), however distinguishing the target of the assessment between father and mother and focusing the dimension autonomy support. Psychometric properties of the measure are addressed as well as measurement invariance analysis regarding father and mother’s parenting behaviors. A total of 664 participants, middle and high school students from six schools located at the districts of Braga and Porto, aged between 12 and 18 years old (M=15.31, SD=1.28), female (54.20%) and male (43.50%), filled in the questionnaire. Results from the confirmatory factor analyses revealed a tridimensional factor structure of QEEP-r, comprised by the factors autonomy support, warmth and knowledge, and adequate psychometric properties. Configural and metric invariance were found for father and mother’s parenting behaviors, but not scalar nor residual invariance. This questionnaire is relevant in the Portuguese language research context regarding parenting behaviors, as it provides a measure of adolescents’ perceptions until the age of 18, through two scales for father and mother’s parenting behaviors with metric invariance.